Arteficiální náhrady kosti - Koníček, Petr (Casopis lekaru ceskych, 2016)
Bone tissue substitutes are divided into basic classification with its pros and cons described. Arteficial bone grafts are especially pointed out in article, publishing our own experience with two specific synthetic preps. Finally there is a blink in the near future of bone tissue augmentation.
Keywords: bone substitute; synthetic bone graft arteficial bone graft.; kostní náhrady; kosti a kostní tkáň; transplantace kostí; lidé; bone graft; Bone and Bones; Humans; Bone Transplantation; Bone Substitutes